Firms' heterogeneity, endogenous entry, and exit decisions - Alexander Totzek (Kiel University, Department of Economics, 2009)
As GDP is highly correlated with both entering and exiting firms, we develop a totally microfounded DSGE model with endogenous firms entry as well as exit decisions. We show that the simplifying assumption of a constant firms' death rate made by the recent literature on DSGE modelling can lead to counterfactual implications of the resulting dynamics. We further demonstrate that the feature of endogenous exits significantly improves the performance of the resulting model when comparing the generated second moments with those of existing models assuming exogenous exits and with the data. Moreover, we estimate the resulting Phillips curve which turns out to be also a function of the change in the mass of producers using the generalized method of moments.
Keywords: E32; E31; 330; Heterogeneity; Producer entry and exit; Business cycles; GMM; Konjunkturtheorie; Markteintritt; Marktaustritt; Allgemeines Gleichgewicht; Dynamisches Gleichgewicht; Stochastischer Prozess; Mikroökonomische Fundierung; Momentenmethode; Phillips-Kurve; Theorie